Body cooling between two bouts of exercise in the heat enhances subsequent performance - Yeargin, S. W.; Casa, D. J.; McClung, J. M.; Knight, J. C.; Healey, J. C.; Goss, P. J.; Harvard, W. R.; Hipp, G. R. (The Journal of Strength and Conditioning Research, 2006)
The purpose was to assess whether body cooling between 2 bouts of exercise in the heat enhances performance during the second exercise session. Using a random, crossover design, 15 subjects (3 women, 12 men; 28 ± 2 years, 180 ± 2 cm, 69 ± 2.3 kg) participated in all 3 trials. Subjects ran 90 minutes on hilly trails in a hot environment (approximately 27;dgC) before 12 minutes of either cold water immersion (CWI; 13.98° C), ice water immersion (IWI; 5.23° C), or a mock treatment (MT) of sitting in a tub with no water (29.50° C). After immersion, subjects ran a 2-mile race. CWI had faster (p < 0.05) performance time (725 seconds) than MT (769 seconds). CWI and IWI had significantly (p < 0.05) lower rectal temperatures postimmersion than MT as well as postrace (p < 0.05). Heart rate also remained significantly lower (p < 0.05) during the CWI and IWI trials for the first half of the race. In conclusion, CWI enhances performance (6% improvement in race time) in the second bout of exercise, supporting its potential role as an ergogenic aid in athletic performance.